Aufklärungserfolg, Zufriedenheit und Verbesserungsmöglichkeiten bei Computertomographie-Aufklärungen - Vogele, D.; Schöffski, Oliver; Efinger, K.; Schmidt, S. A.; Beer, M.; Kildal, D. (Radiologe, 2020)
Background: Providing informed consent before a computed tomography (CT) is important for the physicians and the patients. A personal interview about the procedure, risks, and possible alternatives is mandatory before a CT examination. Methods: A survey was carried out on patient satisfaction with regard to the duration and content of informed consents of CT examinations. Physicians were also interviewed about the duration and content of CT informed consents. Another part of the survey dealt with the acceptance of technical innovations, such as information videos or tablets/PCs. Results: A total of 512 patients and 106 physicians took part in the survey. The duration of the informed consent was estimated by the patients to be 4.08 min on average and 4.7 min by the physicians. The most detailed information given by the physicians regards side effects associated with contrast agents. Less information was given on possible diagnostic alternatives and the need for an examination. According to this, about 92% of all patients did not remember having received information about alternative examinations. Furthermore, 88.7% of the patients and 95.3% of the physicians recommended informed consent using interactive videos and animations, and 74% of the patients and 98.8% of the physicians recommended answering questions on tablet/PC. Conclusion: Patients estimated the duration of a CT informed consent to be a little bit shorter, although some patients did not remember the content very well. The acceptance of technical innovations was very high among the participants. The use of information videos and tablets/PCs could increase the success of providing informed consent.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Content; Electronic patient consent; Informed consent; Patient knowledge; Technical innovations